Parablechnum roraimense and P. paucipinna spp. nov. (Blechnaceae: Polypodiopsida), lectotypification of P. stuebelii, and citation corrections in the family - Dittrich, Vinícius Antonio De Oliveira; Smith, Alan R.; Gasper, André Luís De (Phytotaxa, 2017)
We describe here two new species of Parablechnum from the Neotropics. One of them, P. roraimense, was discovered as a result of visits to the herbaria BM, K, P, PR, and S, as part of the Reflora Project, by the first author. The other new species, P. paucipinna, is from eastern Venezuela. Additionally, we lectotypify a very distinctive Parablechnum, P. stuebelii described from Colombia, now known also from Ecuador and Peru. Finally, we correct five combinations in the family.